PENGARUH KOMPETENSI, MOTIVASI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT SWASTA DI KOTA BATAM - Wasiman (Program Studi Akuntansi, 2021)
This study aims to see the influence of competence, motivation and communication on employee performance at private hospitals in Batam City. The study used a questionnaire distributed to employees of private hospitals in Batam City with a questionnaire of 250 respondents. This study uses an individual level analysis. The research object is employees of private hospitals in Batam City. This study uses multiple linear regression tests which include validity, reliability, normality, and r square tests. The results show that based on the results of the validity test, it shows that all the research indicators show the validity results, which means that it can show to the next stage, and also the reliability test results conclude that all the data collected and processed are reliable. The coefficient of determination (R2) is 0.840, which means that the performance variable can serve the leadership style, motivation and communication variables by 84%, while the remaining is 16%. % evidence by factors not present in this study.